PENGARUH PENGGUNAAN SMARTPHONE SEBAGAI PENUNJANG PEMBELAJARAN IPS DI MASA PANDEMI COVID-19 TERHADAP HASIL BELAJAR - Syariefudin, Muhammad; Barella, Yusawinur; Aminuyati, Aminuyati; Wiyono, Hadi; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2022)
This study examines the effect of smartphones as learning support during the COVID-19 pandemic on junior high school students learning outcomes in social science subjects. The research method used is a quantitative approach in an ex-post facto form. The data collection techniques used were an indirect form of communication using a closed-ended questionnaire, and a documentary study using the final even semester assessment of social science subjects for class VII and class VIII. Based on the data analysis, (1) the use of smartphones to support the learning process during the COVID-19 pandemic has a 58.9% ratio and is categorized as adequate. (2) A total of 56.3% of students have social studies learning outcomes with a predicate of C (adequate). (3) Based on a simple linear regression test, obtained a significance value of 0.919 0.05, showing that Ha is rejected, while H0 is accepted. In conclusion, the use of smartphones as a support for the learning process during the COVID-19 pandemic does not affect the learning outcomes of junior high school students in social science subjects.